THE OVERVIEW OF BELIEFS, ATTITUDE, KNOWLEDGE, AND BEHAVIOR OF HIV/AIDS PREVENTION IN ADOLESCENTS - Haiga, Yuri; Zulkarnaini, Aryaldi; Amelia, Ade Yuli; Zeffira, Laura (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
ABCDE prevention behavior is an attempt to stop the spread of HIV and AIDS. However, there are still many teenagers who do not know about this preventive behavior. This study aims to describe knowledge, attitudes, beliefs, and prevention behaviors regarding HIV/AIDS among adolescents in high school. The methodology employed is cross-sectional descriptive study. Google Form-based data collection technique. This research uses a technique called univariate analysis to analyze the data. The findings revealed that most respondents had a high level of knowledge on HIV/AIDS prevention, while the remainder respondents had a positive attitude toward the topic, strong beliefs about it, and good HIV/AIDS preventative behavior. It is suggested that students actively participate in school activities such as youth care and health services (PKPR).